KAJIAN SISTEM AGRIBISNIS SAYURAN HIDROPONIK DALAM MENUNJANG KETAHANAN PANGAN DI KOTA TARAKAN - Rayhana Jafar; Hamriani Hamriani (J-PEN Borneo : Jurnal Ilmu Pertanian, 2022)
Food security will remain a fundamental problem in meeting the basic needs of the community, not only in rural areas but also in urban areas. Tarakan City is a city located in North Kalimantan and has a population density that causes limited availability of land for agriculture. One solution to overcome this is hydroponic cultivation to support food self-sufficiency in border areas. This study aims to identify and examine through an agribusiness system approach including input subsystems, farming/cultivation, processing, marketing and hydroponic business support services. The research method used is descriptive qualitative through agribusiness systems approach. The method of determining the sample is purposive sampling. The results of this study indicate that hydroponic vegetable farming in Tarakan City that the upstream subsystem includes production facilities and infrastructure such as screenhouses, seeds, nutrition, and agricultural machinery. On Farm subsystem covers an area of 10 x 15 m2 with a total income of Rp.1,373,000, per production. The downstream subsystem includes processing products such as sorting and packing and using a marketing mix approach consisting of two marketing channels. The supporting subsystem consists of government institutions, namely the Food and Agriculture Service, the Industry, Trade and SMEs Service, as well as a private institution, namely PT. Medco. Key words:, Agribusiness, Food Security, Hydroponics